Priority of vaccine-preventable diseases (VPDs) based on routine VPD surveillance using a PAHO-adapted Hanlon method based on Depok City, 2024 - Yuni Kartika; Asri C Adisasmita; Hidayat Nuh Ghazali Djadjuli (Berita Kedokteran Masyarakat, 2026)
Purpose: This situational analysis aimed to identify priority vaccine-preventable diseases (VPDs) in Depok City based on local epidemiological conditions. Methods: Secondary routine data from the Depok City Health Office for 2023–2024 were analyzed, including surveillance reports, immunization coverage data, and outbreak records. Priority setting was conducted using a PAHO-adapted Hanlon based on disease magnitude, seriousness, effectiveness of interventions, inequity, and institutional capacity. Scoring was carried out through discussions with surveillance staff and heads of primary health centers (the five highest and five lowest reported cases among the primary health centers), as well as five representatives from the Depok City Health Office. Results: Diphtheria was identified as the highest-priority VPD with a basic priority rating (BPR) score of 15.49, followed by pertussis (13.61) and rubella (10.37). During 2023-2024, pertussis incidence increased from 7.26 to 14.92 per 1,000,000 population, while rubella incidence rose from 4.15 to 5.97 per 1,000,000 population. Although immunization coverage was relatively high (95.5% in 2023 and 104.91% in 2024), 28.60% of villages did not achieve UCI status in 2023. VPD surveillance system performance in Depok City during 2023–2024 showed mixed results, with improvements in several indicators but persistent gaps in adequate measles–rubella investigation and acute flaccid paralysis (AFP) specimen adequacy. Discussions identified challenges, including staff turnover, health service capacity, workload constraints, training, delayed case follow-up, and delayed recognition of early pertussis symptoms at the primary health care level. Conclusion: Diphtheria, pertussis, and rubella were identified as the highest-priority VPDs in Depok. Context-specific strategies are needed to strengthen surveillance sensitivity, improve immunization equity, and enhance outbreak prevention.